An assessment on the role of universities in pursuing the United Nation‟s sustainable development goal No. 4: the case of Midlands State University. - Mudzengerere, Armstrong (Midlands State University, 2018)
The purpose of this study was to assess the role of universities in pursuing the United Nation’s Sustainable Development Goal No. 4, which is on the need to ensure equitable, inclusive quality education that promotes lifelong learning for all using the case study of Midlands State University. The study takes note that equitable, inclusive quality education that promotes lifelong learning for all is the premise, prudent hallmark to sustainable development and an ideal thread towards the realization of all 17 Sustainable Development Goals .In Zimbabwe Sustainable Development Goals are being implemented under the auspices of the Zimbabwe Agenda for Sustainable Socio Economic Transformation. To analyze this, the study focused on the three variables of SDG4 which are equitable quality education, inclusive quality education and lifelong learning. The study adopted the mixed research method which included in- depth semi structured interviews, participant observation, secondary sources, and open ended and closed ended questionnaires being used as data collection instruments. A mixture of purposive and quota sampling was employed in selecting respondents to inform the study. Study results revealed that Midlands State University since the ratification of the 2030 agenda has embedded inclusive quality education through provision of facilities like the Disability Resource Centre , operationalized equitable quality education through the decentralization policy primed through the multi campus system and has invoked innovation hubs as strategies to expedite lifelong learning to increasingly gravitate towards the realization of Sustainable Development Goal No. 4. The study then proceeds to give conclusions pertaining to the research questions and variables before suggesting recommendations on how the university can continue to aid and abet the implementation of SDG 4.